Intencionalidad e inmaterialidad en Santo Tomás de Aquino - Mayol, Víctor Velarde (Sapientia, 2018)
Several arguments are provided to defend the Thomistic thesis that the essence of knowledge consists in immateriality, against a large sector of contemporary Thomism that prefers to view that the essence of knowledge consists in intentionality. There are two parts to this essay: one historical and the other systematic. The historical part is an attempt to identify the origin of the intentionalist language in contemporary Thomism. It is followed by the systematic part, where it is argued that the Thomistic concept of intentionality not only does not coincide with the modern one, but is relegated to the background in relation to the notion of immateriality. Several reasons are given for this, first, because knowledge by intentionality is simply a type of knowledge, not all knowledge is by intentionality, and, in addition to this, is an imperfect knowledge; second because intentionality is a causal effect; third, because intentionality is not a property of the act of knowledge, but of the form.